ISOLATION AND SELECTION OF ALKALINE PROTEOLYTIC BACTERIA FROM LEATHER PROCESSING WASTE AND ENZYME CHARACTERIZATION - BUDIASIH WAHYUNTARI; NISA R MUBARIK; MARITA ANGGARANi (SEAMEO BIOTROP, 2004)
ABSTRACT The aims of this experiment were to isolate alkaline protease producing bacteria from leather processing waste, and to study the biochemical properties of the enzyme produced by the selected bacteria. Nine bacterial isolates incubated at 37